Luchando! : Cuba's struggle to survive - Patience, Denise (Ethnographic video online, volume 1, 1994)
Consists mostly of interviews with Cubans about their opinions on living in Cuba, its revolutionary process, the blockade by the United States against Cuba and famous Cubans of the past such as José Martí. Also includes Cuban music